Effect of Addition of Urea to The Barley Hay For Production of Gases In Vitro - Dalaf A. Hussein; Ashwaq A.A. Hassan (مجلة الانبار للعلوم البيطرية)
The object of this study were determined the effect of adding urea (0,2%) and molasses (4%) to barley and straw on in vitro gas and methane production, in vitro fermentation characteristic (pH and ammonia nitrogen concentration) and in vitro digestibility, dry matter, organic matter and metabolizable energy, the samples incubated in 39oc water path for 24,48,72 and 96 h., the results indicated that there were significant decrease (p<0.01) in total gas and methane production after 48,72 and 96 h incubation periods in barley straw with 2% urea compared with control (without urea), while 24 h. total gas and methane production increased significant(p<0.01) in straw with 2% urea compared with control. However, metabolizable energy, organic matter digestibility, short chain fatty acids and metabolizable energy for lactation which determine by total gas production after 24 h. incubation increased significantly (p<0.01) in straw with 2% urea compared with no adding urea. The result showed no effects of treatments on pH in all incubation periods except 48h. were pH increased significantly (p<0.01) in compared with control straw with 2% urea .Ammonia nitrogen concentration increased significantly (p<0.01) in straw with 2% urea compared with control after 48h. of incubation period while control treatment increased significantly (p<0.01) after 96h. incubation period compared with straw with 2% urea in ammonia nitrogen concentration, no significant differences found in ammonia nitrogen concentration after 24 and 72 h. incubation period between treatments, moreover, the in vitro dry matter digestibility, organic matter digestibility and metabilizable energy increased significantly (p<0.01) in barley straw with 2% urea compared with control. The result indicated that adding 2% urea to barley straw increased in vitro gas and methane production which lead to increased in vitro organic and dry matter digestibility and metabolizable energy.